Land Rights Disputes In Cianjur Area (Decision No. 3119 K/PDT/2022) - Jesica Jesica; Benny Djaja (Pelopor Publikasi Akademika, 2023)
Land can be granted to individuals who have been provided by the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency to be used and utilized to the best of their ability. The way to obtain land ownership rights to the land is by issuing a tangible evidence by the National Land Agency in the form of a certificate. The National Land Agency has the authority to deal with the land-related issues. One of the land disputes that frequently occurs in society is overlapping. The purpose of this research is to determine the process of resolving land pwnership disputes in the Cianjur region. The research findings indicate that the causes of overlapping are negligence of surveying officers from the Land Office or the National Land Office and the lack of public awareness among the community, especially landowners, to utilize and use their land according to the purpose of granted rights, as well as the failure to mark the boundaries of the land. This study uses normative legal research methods with a statute approach, uses secondary data types with data collection techniques, namely literature review, as well as using legal descriptive analysis